The Influence of Religiosity on Repurchase Intention with Perceived Behavioral Control and Brand Image as Connecting Factors - Yesa Ramadhani; Kusyana Kusyana; Mutdi Ismuni (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The competition that occurs between similar drinking water products and the boycott against buying Aqua drinking water products is a challenge for the Aqua company. This research aims to determine the influence of religiosity on the intention to repurchase Aqua drinking water products with perceived behavioral control and brand image as mediation and moderation. Research was conducted on 254 Aqua consumers. Sampling was carried out using purposive sampling, namely respondents who had consumed Aqua drinking water products at least twice. The data analysis method was carried out using PLS SEM. The research results found that religiosity had a negative impact on the intention to repurchase Aqua drinking water products. Religiosity has a positive impact on perceived behavioral control and brand image. Perceived behavioral control and brand image positively mediate the influence of religiosity on intention to repurchase Aqua drinking water products. Perceived behavioral control positively moderates the influence of religiosity on intention to repurchase Aqua drinking water products. Negatively moderating brand image the influence of religiosity on intention to repurchase Aqua drinking water products. Future research can be limited to certain religions, ages, and regions.